2007
DOI: 10.1111/j.1745-3933.2007.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

A model of cometary outbursts based on the idea of fragmentation of ice grains

Abstract: In this Letter the mechanism of destruction of ice grains as the cause of cometary outbursts and variations of brightness is reviewed. Such destruction can arise from the combination of two causes: inclusions of chemical compounds that are much more volatile than water‐ice placed inside cometary water‐ice grains; and the influence of the solar wind on such heterogeneous grains. Numerical calculations have been carried out for a large range of values of probable physical characteristics of cometary material. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
(45 reference statements)
1
9
0
Order By: Relevance
“…Taking the obtained results into consideration we conclude that the critical heliocentric distance of a comet d cr is increasing function of the parameter f as well as the value of the modulus of the grains electrostatic potential | V |. We can calculate the simulated changes of the cometary brightness in a similar way as in the paper of Gronkowski (2007b). In that paper and references therein numerical problems related to the calculation of the changes in the cometary brightness induced by the grain fragmentation are described in detail.…”
Section: The Quantitative Description Of Grain Fragmentationmentioning
confidence: 89%
See 4 more Smart Citations
“…Taking the obtained results into consideration we conclude that the critical heliocentric distance of a comet d cr is increasing function of the parameter f as well as the value of the modulus of the grains electrostatic potential | V |. We can calculate the simulated changes of the cometary brightness in a similar way as in the paper of Gronkowski (2007b). In that paper and references therein numerical problems related to the calculation of the changes in the cometary brightness induced by the grain fragmentation are described in detail.…”
Section: The Quantitative Description Of Grain Fragmentationmentioning
confidence: 89%
“…Unfortunately as the previous electrostatic destruction this mechanism generally gives small changes in the cometary luminosity and cannot be the source of outbursts in a general way as was shown www.an-journal.org by Gronkowski (2001). Recently (Gronkowski 2007b), it was shown that the cometary grains can undergo simultaneously the electrostatic destruction as well as the thermodynamic fragmentation, and this total fragmentation can be the source of essential changes in the cometary brightness. In some way the presented paper is the development of the above mentioned author's work which was only the qualitative approach to the problem of grain fragmentation.…”
Section: Thermodynamical Fragmentationmentioning
confidence: 93%
See 3 more Smart Citations